Effects of ipil ipil and calcium dietary sources on egg and growth performances of Japanese quail (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
This study was carried out in the Department of Physiology and Pharmacology at Hajee Mohammad Danesh Science and Technology University to evaluate the effect of ipil ipil and calcium supplementation on egg production and live body weight of Japanese quail. Forty two days old “Japanese Quail” were divided into four groups (n=10 birds in each group). Group T0 was considered as control, fed only with commercial layer ration. Group T1 was additionally supplemented with 2 g grinded ipil ipil leaves, Group T2 with 2 g Dietary Ca sources and Group T3with 2 g grinded ipil ipil leaves with 2 g dietary Ca sources per kg feed. Observations were recorded for growth performance, egg production and egg quality of Japanese quail. Body weight (g) was increased significantly (p